Audiogames: (re)pensando jogos digitais acessíveis para crianças com deficiência visual - Santos, Cleusa da Silva (2024)
Contemporary society has undergone significant changes in recent times, among which advances in the area of Digital Information and Communication Technologies (DICTs) can be highlighted. The technological world offers its users a plethora of innovations, with digital games being one of them. Currently, these games are increasingly occupying the time of children and young people as part of an informal educational process, providing various forms of interaction and learning. The primary objective of this study was to design and develop audiogames using the Scratch platform, specifically for use by children with visual impairments. This study employed qualitative research methods, utilizing an exploratory approach and applied nature. The evaluation of the audiogames comprised two distinct phases: (1) an inspection evaluation conducted with five teachers specializing in Visual Impairments, two of whom were blind; and (2) gameplay tests conducted with two blind girls, aged 10 and 12, who are members of the Association of the Visually Impaired and Blind of Cachoeira do Sul/RS. In addition to the games, a Digital Audiogames Almanac was created as a technical product. The study concluded that the Scratch platform, known for its ease of use and flexibility, successfully facilitated the creation of audiogames that achieved the initial objectives of the research. A unique aspect of our research is that the audiogames are available in different versions, enabling both online and offline play; in the latter case, installing the game application is recommended. This study aims to contribute to the dissemination of accessibility resources in digital games and to stimulate future research by professionals interested in this field.